2013
DOI: 10.1038/nchembio.1257
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors that stabilize a closed RAF kinase domain conformation induce dimerization

Abstract: RAF kinases play a prominent role in cancer. Their mode of activation is complex, but critically requires dimerization of their kinase domains. Unexpectedly, several ATP-competitive RAF inhibitors were recently found to promote dimerization and transactivation of RAF kinases in a RAS-dependent manner and as a result undesirably stimulate RAS/ERK-mediated cell growth. The mechanism by which these inhibitors induce RAF kinase domain dimerization remains unclear. Here we describe BRET-based biosensors for the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
177
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(187 citation statements)
references
References 51 publications
(80 reference statements)
10
177
0
Order By: Relevance
“…Sorafenib-induced B-/C-Raf heterodimers have been linked to specific increases in the nanoscale clustering of oncogenic K-ras4B (here, K-ras) (60,61), which resides in acidic lipid nanodomains (62). While evidence for the localization of SPRED1 to acidic lipid domains exists (55), details on the composition are not known.…”
Section: Resultsmentioning
confidence: 99%
“…Sorafenib-induced B-/C-Raf heterodimers have been linked to specific increases in the nanoscale clustering of oncogenic K-ras4B (here, K-ras) (60,61), which resides in acidic lipid nanodomains (62). While evidence for the localization of SPRED1 to acidic lipid domains exists (55), details on the composition are not known.…”
Section: Resultsmentioning
confidence: 99%
“…1C). Using the biosensor assay to screen a drug library, Lavoie et al 26 further found that certain ATP-competitive inhibitors for BCR-ABL, p38, and VEGFR also promote Raf dimerization. In addition, these inhibitors induced the paradoxical activation of ERK, indicating the clinical importance of screening kinase-targeted drugs for their potential to promote Raf dimerization.…”
Section: Revisiting Raf Dimerization In Human Disease Statesmentioning
confidence: 99%
“…Therrien and Sicheri has recently provided key insight regarding how the ATP-competitive Raf inhibitors promote Raf dimerization. 26 Protein kinase domains consist of N-and C-lobes, and due to their dynamic nature, there is a significant degree of flexibility between the N-and C-lobes as well as within the N-lobe itself. The side-to-side dimer interface spans both the N-and C-lobes, and by binding the ATP pocket, Lavoie and coworkers 26 found that the inhibitors stabilize the closed conformation of the kinase domain, thus generating a static dimer interface surface that is conducive for dimerization.…”
Section: Revisiting Raf Dimerization In Human Disease Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…These considerations gain further relevance in the light of recent insights into the Ras-dependent activation mechanism of Raf. A wealth of experimental data has recently established that Raf kinases function as homo-and heterodimers [57][58][59][60]. Although many details of Raf regulation remain obscure it is evident that only the dimeric form is responsive and sensitive to activation by Ras-GTP [57].…”
Section: Discussionmentioning
confidence: 99%